A Foucauldian ethics of positivity in initial teacher education - Karnovsky, Saul; Gobby, Brad; O’Brien, P. (2021)
This article explores ways pre-service teachers learn to work upon their positive emotional conduct during an initial teacher education course. The article argues that education practice today promotes the acting out of positive emotions, creating conditions within which pre-service teachers ethically shape their emotional conduct. Utilising Foucault’s four-part ethical framework, the article draws on longitudinal research of pre-service teachers in Western Australia to analyse the crafting of emotional conduct through techniques of the self. The techniques the participants came to employ during their course learning aligned with a telos of the resourceful, positive, and professional teacher. The article argues that this ethical enterprise relies on a certain model of teacher subjectivity which is inseparably linked with normalising governmental power. Such disciplining of emotions, however, is neither one-dimensional nor deterministic; rather, work at the intersection of the government of others and of oneself. We argue this allows pre-service teachers the freedom to care for the self as they seek to foster their own ethical practices as teachers.